GENDER DIFFERENCES OF STUDENTS’ WRITING ABILITY IN DESCRIPTIVE TEXT - Wiyanto, Muhammad Saibani; Asmorobangun, Panji Wisnu (UNDIKMA Mataram (Eks. IKIP Mataram), 2020)
Language has an important role to a group of people. The connection between language and society is called sociolinguistic. Nowadays, sociolinguistic has involved many significant research topics. One of them is gender and language. Studies about gender differences have been done for many years in EFL context. The current article analyze gender differences in senior high school students writing ability. The purpose of this article is to find the linguistics features that male and female students tend to use and to find out the gender differences reflected on the students writing ability. The article used qualitative design and document analysis article as the approach based on Ary et al. (2010). The subject of this article was one class of X MIPA 2 at MAN 6 Jombang. The source of the data is students writing assignments, while the data is the word that were wrote by all of the students in class X MIPA 2 which is contain the types linguistics features based on Mulac theory. The article found 4 linguistics features use by students. The finding was most used linguistics features in their descriptive text is locative and reference to quantity. That the purpose was to show the location of the object and to show the amount of something.